Virtual Tour Media to Support Digital Literacy Culture in Learning The History of The Spice Route - Ahmad Alim Wijaya; Sariyatun; Sudiyanto (Jurnal Pendidikan Indonesia, 2025)
The current problem is the lack of reading materials and learning media related to the context of the spice route, both locally and nationally. Educators tend to convey spice route material briefly by inserting the material with a broader scope so students' understanding is lacking. This study aims to develop a virtual tour media for the spice route in filling the availability of interactive media to form a digital culture in history learning. This type of development research uses the ADDIE approach model involving various media and material experts. The data collection technique uses a quantitative approach with percentage analysis. The sample used in this study was class X students at SMAN. The data collection method uses a questionnaire. The data collection instrument uses a questionnaire sheet. The data analysis technique uses qualitative and quantitative descriptive analysis. The analysis results show that media experts give an average score of 3.7 (very good). Meanwhile, media experts gave an average score of 3.4 (very good). Then, for the acquisition of user trial scores, 2.9 (good) was used for limited group tests, 3.3 (very good) was used for medium group tests, and 3.7 (very good) was used for broad group tests. The study results show that after a series of testing processes were carried out on the virtual media of the spice route, the media is feasible and can be used in class X as an alternative tool for presenting interactive and timeless history learning.